IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS VIII DI SMPN 7 DENPASAR - Mutiara, Ayu; Sutriyanti, Ni Komang; Muniksu, Made Sukma (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Improving the quality of education in Indonesia can be carried out through the implementation of the right curriculum in educational units. The implementation of the independent curriculum can improve the quality of education. The objectivitas of this study are to (1) understand the form of implementation of the independent curriculum, (2) identify the obstacles that arise and the efforts made to overcome the obstacles faced during the implementation curriculum, and (3) find out the implications of implementing the independent curriculum. Data collection methods were structured non-participant observation, semi-structured interviews, literature study, and documentation, then analyzed using qualitative descriptive analysis metods by reducing data, presenting data, and conclusion. The results of this research show (1) the form of implementing the independent curriculum at SMP Negeri 7 Denpasar is an independent curriculum that has changed, (2) the obstacles that arise are that students are not used to learning the independent curriculum, teachers experience problems with limited LCDs and projectors to support learning, and the school principal lack of comprehensive understanding of the independent curriculum. Efforts to overcome student obstacles by providing reflection, material conclusions, enrichment and remedial, teachers overcome obstacles by utilizing learning applications such as Google Forms, Quizzizz, Kahoot, and attending training, and school principals overcome obstacles by attending workshops and seminars, (3) implications can form good character in accordance with the Pancasila Student Profil.